Total Penectomy for Recurrent Chordoma of the Corpus Cavernosum. (13th February 2020) - Eismann, Lennert; Kess, Sabine; Stief, Christian G.; Strittmatter, Frank
Abstract : Chordomas are rare low malignant neoplasm arising from remnants of the notochord with predilection site of the clivus or the os sacrum. Standard therapy is radical excision and adjuvant radiation. Due to invasive growth and adjacent to vital structures resection is often incomplete, and therefore, local recurrence is frequent. First, to the best knowledge of our authors, we present a 70-year-old man with a recurrent chordoma infiltrating the corpus cavernosum. Asymptomatic recurrence was diagnosed by magnet resonance imaging according to the standard follow-up. Our interdisciplinary tumor board recommended surgical resection. We performed a total penectomy and perineal urethrostomy to achieve negative resection margins and preserve best quality of life for the patient.